Geriatric Health Problems and Health Care Seeking Practice Among Elderly People Attending One Selected Geriatric Hospital - Begum, Mahjabeen Sultana (Bangladesh Journal of Physiology and Pharmacology, 2010)
A vast majority of the elderly Bangladeshi people is suffering from various health problems, however, health care services are insufficient to cope with the problem. This study tried to find out about the geriatric health problems and health care seeking practice attending a selected hospital in Dhaka city. The information collected may help provide adequate guideline to help the elderly to overcome old age health problems. This was a cross sectional study and included 107 respondents aged 60 years and above. The study was carried out during March June, 2001, at Prabin Hitayishi Hospital, Bangladesh Association of Aged and Institute of Geriatric Medicine (BAAIGM), Agargaon, Sher e Bangla Nagar, Dhaka. Out of 107 respondents, 46.7% were aged 65 years or above, 67.3% were married, 14% were living with spouse, 23.4% were employed, 46.7% had self income and 19.6% were living in families with 9 or more members. Knowledge about old age diseases were limited to diabetes (57.9%), high blood pressure (53.3%), heart diseases (50.4%), respiratory diseases (31.8%), and orthopaedic diseases (3.7%), and 41.1% had no knowledge. Regarding health care knowledge, 67.3% had knowledge about self health care, 29.9% were on regular check up and 78.5% attended hospital. Morbidity pattern showed that most of the respondents (23.4%) had orthopaedic problems, followed by eye (21.5%), dental (12.4%), ENT (12.1%), respiratory (9.3%), gastrointestinal (7.5%), diabetes (2.8%) and neurological (2.8%). Six respondents had multiple diseases. Specific diseases in orthopaedic group (n=25) were spondylitis (60%), rheumatoid arthritis (20%) and osteoporosis, osteomyelitis, backpain and frozen shoulder (20%); in eye disease group (n=23) were refractory error (34.8%), conjunctivitis (30.4%), cataract (17.4%) and presbyopia (17.4%); in dental disease group (n=14) were loose teeth (78.5%) and dental caries (21.4%); in ENT disease group (n=14) were CSOM (57%), tinnitus (35%) and vertigo and hearing loss (7.1%); in cardiovascular group (n=13) were hypertension (84%) and old myocardial infarction and ischaemic heart disease (15.3%); and in respiratory disease group (n=10) were pharyngitis sinusitis (60%), bronchial asthma (20%) and bronchitis (20%). Health care seeking pattern was orthopaedic 40% (n=25), eye 13% (n=23), dental 14.3% (n=14), ENT 21.4% (n=14), cardiovascular 38.5% (n=13), respiratory 40% (n=10), gastrointestinal 25% (n=8), endocrine 66.7% (n=3) and neurological 33.3 (n=3). Most of the elderly did not seek health care from hospital or clinic. Key words: Health care; Elderly DOI: 10.3329/bjpp.v23i1.5727 Bangladesh J Physiol Pharmacol 2007; 23(1&2) : 20-24